ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SUMATERA SELATAN - Nita Darma Sari (Department of Development Economics, Universitas Sriwijaya, 2005)
This research is aimed to describe some variables influence the Vehicle Tax Revenues. Analysis used in this research was Quantitative analysis and formulated in a Quadratic Regression Model. The output shows that variables influence vehicle tax revenues were per capita income, vehicles sums, vehicles tax tariff and inflation simultaneously significant to Vehicle Tax Revenues in coefficient correlation = 0,999 (99,9%). The output regression was positive and significant to vehicles sums and vehicles tax tariff, whereas per capita income and inflation were insignificant as statistic. Keywords: vehicle sums, vehicle tax tariff, inflation.